Ethical Considerations in Water Management Systems - Llamas, M. Ramon (Water Nepal, 2003)
Water management decisions have many facets including planning, regulating, designing, construction, operation, maintenance and cost allocation. Decisions might be variously considered wrong or right according to the system of values espoused by a society. Many consider that universal ethical principles exist, such as those embodied in the United Nations Declaration of Human Rights of 1948. It is considered that practical ethical principles in water activities evolve from the concepts of human dignity and human sociability. Most water problems are caused by a lack of equilibrium between its utilitarian (economic) value which is connected to human sociability and its intangible or sacred values which are related to human dignity. The application of these principles may generate legitimate but different practical solutions because of the complexity of water uses (urban, irrigation, energy etc.) and the great variability of water needs and values, physical and social, geographical and historical. The solidarity principle should inform the relations between upstream and downstream water users and between countries in international watersheds. It also is the basis for the concept of sustainability, i.e. solidarity towards future generations. The subsidiary principle recommends that decisions should be made at the lowest social level compatible with the common good. Coordination among family groups, municipalities, countries, states and federal institutions is crucial but not easy to achieve. The participation of all stakeholders is deemed a must but in practice the application of this principle face may serious obstacles because many stakeholders are poorly educated and informed. The main obstacles to the implementation of ethical principles in water management are described under the following concepts: ignorance, arrogance, institutional inertia and corruption. Case histories from Spain, the most arid country in Europe, will be shown as examples of ethical-or unethical-solutions. Water Nepal Vol.9-10, No.1-2, 2003, pp.13-27